PENGARUH PACKAGING DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN KOPI BUBUK DI DESA TANAH HITAM - Onsardi Onsardi; Septian Bayu Mantovani (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
The title of this research is the Effect of Packaging and Social Media Marketing on the Decision to Purchase Ground Coffee in Tanah Hitam Village. Where this study aims to analyze the effect of packaging and social media marketing on purchasing decisions.The object of this research is the consumers of ground coffee in the Tanah Hitam area, with the sample collection method in this study using the formula Hair, et al (2010). Where the minimum sample size is 5-10 times the indicator variable, where the indicator variable in this study is 13 times 10 or the maximum sample size from the formula Hair, et al (2010). By using multiple linear regression analysis technique, it can be concluded that the variables of Packaging and Social Media Marketing have a significant effect on purchasing decisions Keywords: Packaging, Social Media Marketing, Purchase Decision.